"Drop-in" fuel production from biomass: Critical review on techno-economic feasibility and sustainability. (January 2021) - Kargbo, Hannah; Harris, Jonathan Stuart; Phan, Anh N.
Abstract: This paper reviews the technological and economical feasibilities as well as sustainable assessment of approaches (thermochemical and biochemical) applied for sustainable "drop-in" fuel production from lignocellulosic sources. The challenges for each pathway to produce "drop-in" fuels are covered. Currently "drop-in" fuel production cost is approximately 2 times (~5–6$/gallon) higher than fossil fuels (3$/gallon), especially with the use of 2nd generation feedstocks. The primary sources of cost with "drop-in" fuel production are feedstock cost (40–60% of the total production cost), syngas cleaning and conditioning to meet Fischer-Tropsch synthesis requirement (12–15% of the total production cost) and bio oil upgrading (14–18% of the total production cost) in the case of pyrolysis and hydrothermal liquefaction (HTL). The most influential factors on the life cycle analysis (LCA) were biomass cultivation, harvesting, biomass pre-treatment, and transportation. Therefore, robust processes that can use local waste biomass are far more environmental and economically viable, especially as biofuel from second generation have a greater potential to reduce greenhouse gas emissions (50–100%) than first generation biofuels (50–90%) when land use changes are omitted in the LCA. The sustainability of biofuels is pre-dominantly dependant on the sustainability of the initial biomass, with 2nd generation feedstocks being more sustainable than 1st generation. Gasification-FTS is considered as the most promising technique for "drop-in" fuel production over pyrolysis and HTL due to its flexibility towards feedstock acceptance and the ability to produced high yields of liquid fuel together with other economically viable biofuels such as electricity and heat. Biochemical routes (i.e.fermentation) to "drop-in" fuels are still in their early development stages, and therefore require more studies and pilot-scale experiments in order to discover an economic and sustainable means of using these methods. Graphical abstract: Image 1 Highlights: "Drop-in" fuel production cost is currently ~2times higher than fossil fuels with the use of second-generation feedstock. The most influential factors on the LCA were biomass cultivation, harvesting, biomass pre-treatment, and transportation. Gasification-FTS shows promises for "drop-in" fuel production for its feedstock tolerance and high selectivity to liquid fuel. Fermentation to "drop-in" fuels is still in the early development stage.